Protecting the Rights of Refugees in Latin America: The Evolution of Regional Humanitarian Diplomacy (1984—2014) - O. N. Bogatyreva (Научный диалог)
The mechanisms of regional cooperation of the countries of Latin America and the Caribbean on the development of the system of reception of refugees and protection of their rights during 1984—2014 are considered. Attention is paid to regional traditions, the dualism of refuge models in Latin America is noted. The issues of legal regulation  of the institution of refuge in regional documents are touched upon. It has been established that the evolution of the refugee reception system in the region took place in the framework of the convergence of international law governing human rights, international humanitarian law and international refugee law. It is shown that the improvement of the institution of refuge was not limited to the instruments of classical diplomacy. It is reported that through the efforts of nongovernmental organizations, academia and official diplomacy in the course of negotiations at regular regional forums, a common system of sharing joint responsibility for the protection of refugees in Latin America and the Caribbean was created. The author defines this cooperation as multilateral humanitarian diplomacy aimed at protecting persons displaced as a result of armed conflicts and massive violence in the region, mainly in Central America. The main milestones in the development of regional humanitarian diplomacy related to the establishment of principles and standards for resolving crisis situations with refugees are highlighted.